Labor's Liquidity Service and Firing Costs - Bennett, Herman (IMF Working Papers; Working Paper ;, 2007)
This paper proposes a new effect of firing costs on firms' behavior that builds from firms' demand for liquidity. When a time gap exists between production and its associated revenues, firing can become a liquidity adjustment tool that allows firms to increase their short-term liquidity. I refer to this feature as labor's liquidity service. The presence of firing costs reduces the value of labor's liquidity service, which affects firms' demand for liquidity, and thus, firms' demand for inputs. In addition to this negative effect at the creation margin, I also show that firing costs imply relatively higher destruction for financially restricted firms. I present a model that develops these ideas and show that the presence of firing costs has a stronger negative effect on production levels of firms facing liquidity constraints. Regression analysis, based on country industry panel data sets, provides empirical evidence in line with the liquidity service effect of firing costs proposed. I reject the hypothesis that the effect of firing costs does not depend on the presence of financial restrictions. I find a relatively stronger negative effect of firing costs on the output of industries with higher liquidity requirements and a relatively stronger negative effect of firing costs on the output of small firms.